A Design of Vertical Polarized Conformal Antenna and Its Array Based on UAV Structure - Zhang Wei; Yang Junfeng (International Journal of Antennas and Propagation)
The designs of conformal antenna and its array usually need to combine with different carrier structures. As for cone or cylindrical carrier, through using of invasive weed optimization (IWO), the conformal array should be the optimized design as the antenna installation space requirements of cylindrical carrier; through adopting the antenna unit miniaturization method, it designs out a conformal antenna and makes it easier to be installed and the omnidirectional circular polarized beam is also realized. As for unmanned aircraft carrier, it designs out the low profile of conformal vertical polarization antenna unit; through using the electric field integral equation (EFIE) and electric/magnetic current combined-field integral equation (JMCFIE) and multilevel fast multipole algorithm (MLFMA), it analyzes the two different characteristics of unmanned aircraft carrier on the influence of antenna performance. The results obtained through experiments and JMCFIE analysis are in good agreement; according to unmanned aircraft carrier, it also designed out the antenna in X/K-band spectrum; through IWO, the antenna array is optimized; the test results show that the array scanning angle can reach the corresponding beam direction.